Hubungan sikap perawat dengan penerapan patient safety pada masa pandemi Covid 19 - Usastiawaty Cik Ayu Saadiah Isnainy; M Ricko Gunawan; Rafika Anjarsari (Holistik Jurnal Kesehatan, 2021)
Clinical nurses' attitude toward patient safety: application and results during Covid 19 pandemicBackground: Patient safety is an effort to reduce unnecessary injuries associated with health care to the minimum acceptable level. Patient safety incident report in Indonesia in 2009 were 114, 103 incident in 2010, 34 incident in 2011. The number of adverse events was 10.5% and a near miss incident  was 6.15%.Purpose: known that relationship between nurses' attitude with patient safety application during the Covid-19 pandemic at public health center Pesawaran district in 2020.Method: A quantitative study by survey analytical with cross-sectional design. The sampling technique using a questionnaire and taken by total sampling. The respondents of 40 clinical nurses at public health centre.Results: Respondents who had positive attitudes were 32 (80%), and who had negative attitudes was 8 (20%). Respondents who had behavior of patient safety standard application with good categories were of 20 (50%), and respondent with a poor category was of 20 (50%) and based on the statistical result of (p value 0,008; OR=15,000).Conclusion: There are relationship between clinical nurses' attitude toward patient safety: application and results during COVID-19 pandemic at the health center. Suggestions for health centre management to pay attention for patient during covid-19 pandemic and all staff nurses to follow the health protocol for Covid.Keyword : Clinical nurses; Attitude; Patient safety; Application; Covid-19 pandemicPendahuluan: Keselamatan pasien merupakan sebuah upaya menurunkan cedera yang tidak perlu yang berhubungan dengan pelayanan kesehatan hingga ke tingkat minimum yang dapat diterima. Laporan insiden keselamatan pasien di Indonesia tahun 2009 sebanyak 114, tahun 2010 sebanyak 103, tahun 2011 sebanyak 34. Angka Kejadian Tidak Diharapkan (KTD) sebesar 10,5% dan Kejadian Nyaris Cedera (KNC) sebesar 6,15%.Tujuan: Diketahui hubungan sikap perawat dengan penerapan patient safety pada masa pandemic covid 19 di UPT Puskesmas Rawat Inap Kabupaten Pesawaran Tahun 2020.Metode: Penelitian ini menggunakan desain penelitian Survey Analitik dengan menggunakan rancangan cross-sectional. Teknik pengambilan sampel dalam penelitian ini menggunakan lembar kuesioner. Populasi dalam penelitian ini adalah seluruh perawat puskesmas rawat inap yang berjumlah 40 responden.Hasil: Responden yang mempunyai sikap positif sejumlah 32 (80%) dan responden dengan sikap negatif sejumlah 8 (20%). Responden yang mempunyai perilaku penerapan standar keselamatan pasien dengan kategori baik sejumlah 20 (50%) dan responden dengan tingkat perilaku tidak baik sejumlah 20 (50%). Uji penelitian yang dilakukan menggunakan uji chi square dengan hasil (p value 0,008; OR=15,000).Simpulan: Ada hubungan sikap dengan penerapan patient safety pada masa pandemi covid 19 di UPT Puskesmas Rawat Inap Kabupaten Pesawaran tahun 2020. Saran dari peneliti ini diharapkan untuk selalu menerapkan standar keselamatan pasien dalam pelayanan.